2020
DOI: 10.1002/ajh.25800
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of iron supplementation following blood donation vary with baseline iron status

Abstract: Whole blood donation rapidly removes approximately 10% of a donor's blood volume and stimulates substantial changes in iron metabolism and erythropoiesis. We sought to identify donors who benefit from iron supplementation, describe the nature of the benefit, and define the time course for recovery from donation. Blood samples were collected over 24 weeks following whole blood donation from 193 participants, with 96 participants randomized to 37.5 mg daily oral iron. Changes in total body, red blood cell (RBC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…This result echoes findings that a donation interval of 56 days is insufficient time for the donor to replete the iron loss through donation, and that iron deficiency in high-frequency donors is common. [33][34][35][36][37][38] Maintaining a threshold of 15 ng/ml for ferritin levels would imply mean donation frequencies of 1.9 per year for women and 4.1 per year for men. Currently maximum donation frequencies are three and five per year, which implies that such a target would have a substantial impact on donor availability.…”
Section: Discussionmentioning
confidence: 99%
“…This result echoes findings that a donation interval of 56 days is insufficient time for the donor to replete the iron loss through donation, and that iron deficiency in high-frequency donors is common. [33][34][35][36][37][38] Maintaining a threshold of 15 ng/ml for ferritin levels would imply mean donation frequencies of 1.9 per year for women and 4.1 per year for men. Currently maximum donation frequencies are three and five per year, which implies that such a target would have a substantial impact on donor availability.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that rates of donor deferral due to low-Hb are considerably less in those taking iron supplements, both at the first donation visit and at subsequent donations. [44][45][46][47][48] Only providing donors with information about their (low) ferritin level does not seem to increase their iron intake. 15 The beneficial effects of iron supplementation may be counteracted by more frequent adverse events in donors who receive iron supplementation, which is likely to limit acceptability and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that donors with ferritin <12, 12-50, and >50 ng/ml have distinctly different responses to oral iron supplementation following whole blood donation suggesting that these ferritin strata define different degrees of functional iron deficiency. 24 Therefore, these strata were used to correlate donor iron status with pica behaviors (Table 2). Among those chewing ice, 27% (331 of 1240) had ferritin <12 ng/ml, while 18% (1818 of 10,102) of those not chewing ice had ferritin <12 ng/ml (χ 2 = 56.89, p < .001).…”
Section: Pica Behaviors Were More Prevalent In Donors With Low Ferritinmentioning
confidence: 99%
“…Similar trends were observed among those eating greater than 8 oz of ice at least once a day (χ 2 = 48.12, p < .001). Non-ice substances chewing that were reported include, but not limited to (may overlap), clay (9), dirt (7), starch (15), raw pastas (73), chalk (8), coal (1), paper (38), or other substances (24). Among those chewing non-ice substances, 30% (38 of 129) had ferritin <12 ng/ml, while 19% (2108 of 11,212) of those not chewing non-ice substances had ferritin <12 ng/ml (χ 2 = 10.69, p = .005).…”
Section: Pica Behaviors Were More Prevalent In Donors With Low Ferritinmentioning
confidence: 99%
See 1 more Smart Citation